Designing an agricultural vegetative waste-management system under uncertain prices of treatment-technology output products. (May 2018) - Broitman, D.; Raviv, O.; Ayalon, O.; Kan, I.
Highlights: An economic optimization model for vegetative waste from agriculture was developed. The model accounts for uncertain and fluctuating output product prices. Risk-neutral and risk-averse sensitivity analyses of the system were performed. The ranking of the feasible treatment technologies is found under both risk approaches. Uncertain prices' impact is a function of their average and coefficient of variance. Abstract: Setting up a sustainable agricultural vegetative waste-management system is a challenging investment task, particularly when markets for output products of waste-treatment technologies are not well established. We conduct an economic analysis of possible investments in treatment technologies of agricultural vegetative waste, while accounting for fluctuating output prices. Under a risk-neutral approach, we find the range of output-product prices within which each considered technology becomes most profitable, using average final prices as the exclusive factor. Under a risk-averse perspective, we rank the treatment technologies based on their computed certainty-equivalent profits as functions of the coefficient of variation of the technologies' output prices. We find the ranking of treatment technologies based on average prices to be robust to output-price fluctuations provided that the coefficient of variation of the output prices is below about 0.4, that is, approximately twice as high as that of well-established recycled-material markets such as glass, paper and plastic. We discuss some policy implications that arise from our analysis regarding vegetative waste management and its associated risks.